Bark and ambrosia beetle (Coleoptera: Scolytidae) responses to volatiles from aging loblolly pine billets - Flechtmann, C. A.H. [UNESP]; Dalusky, M. J.; Berisford, C. W. (Oxford University Press (OUP), 1999)
Many species of bark and ambrosia beetles use host volatiles as cues for breeding site location. In a study where the objectives were to identify the different volatiles released by Pinus taeda L. billets as they age, to determine the arrival sequence of scolytids (Coleoptera: Scolytidae), and to correlate volatile emission by the billets with beetle catches, 25 species of scolytids were trapped. Bark beetles were more attracted to the billets in the beginning of the period, whereas ambrosia beetles arrived later. Among the bark beetles, Dendroctonus terebrans (Olivier) was significantly more attracted during the 1st 3 wk after tree felling, Hylastes tenuis Eichhoffin the 1st 2 wk, Pityophthorus pulicarius (Zimmermann) in weeks 2 and 3, and Ips grandicollis (Eichhoff) was more attracted on weeks 3 and 4. Among the ambrosia beetles, Xyleborinus saxeseni (Ratzeburg) was more attracted to billets during weeks 4-6, whereas Xyleborus pubescens Zimmermann and Xyleborus californicus Wood were more attracted during week 6. The billets showed marked decline in attractiveness to all scolytids after 8 wk. Volatiles collected during the beetle trapping periods included 15 hydrocarbon monoterpenes, 18 oxygenated monoterpenes, 4-allylanisole, and ethanol. The hydrocarbon monoterpenes and 4-allylanisole decreased sharply over time, but oxygenated monoterpenes and ethanol increased up to weeks 4-6, after which they also decreased. Good correlations between certain billet volatiles and catches for some beetle species were obtained, but their biological significance could not be determined.
Keywords: Arrival sequence; Correlation; Ethanol; Hydrocarbon monoterpenes; Oxygenated monoterpenes; Scolytidae